Meeting report from the Prostate Cancer Foundation PSMA theranostics state of the science meeting. Issue 15 (31st August 2020) - Miyahira, Andrea K.; Pienta, Kenneth J.; Babich, John W.; Bander, Neil H.; Calais, Jeremie; Choyke, Peter; Hofman, Michael S.; Larson, Steven M.; Lin, Frank I.; Morris, Michael J.; Pomper, Martin G.; Sandhu, Shahneen; et al.
Abstract: Introduction: The Prostate Cancer Foundation (PCF) convened a PCF prostate‐specific membrane antigen (PSMA) Theranostics State of the Science Meeting on 18 November 2019, at Weill Cornell Medicine, New York, NY. Methods: The meeting was attended by 22 basic, translational, and clinical researchers from around the globe, with expertise in PSMA biology, development and use of PSMA theranostics agents, and clinical trials. The goal of this meeting was to discuss the current state of knowledge, the most important biological and clinical questions, and critical next steps for the clinical development of PSMA positron emission tomography (PET) imaging agents and PSMA‐targeted radionuclide agents for patients with prostate cancer. Results: Several major topic areas were discussed including the biology of PSMA, the role of PSMA‐targeted PET imaging in prostate cancer, the physics and performance of different PSMA‐targeted PET imaging agents, the current state of clinical development of PSMA‐targeted radionuclide therapy (RNT) agents, the role of dosimetry in PSMA RNT treatment planning, barriers and challenges in PSMA RNT clinical development, optimization of patient selection for PSMA RNT trials, and promising combination treatment approaches with PSMA RNT. Discussion: This article summarizes the presentations from the meeting for the purpose of globally disseminating this knowledge to advance the use of PSMA‐targeted theranostic agents for imaging and treatment of patients with prostate cancer.